2016
DOI: 10.1158/2326-6066.cir-16-0011
|View full text |Cite
|
Sign up to set email alerts
|

Can Targeting Stroma Pave the Way to Enhanced Antitumor Immunity and Immunotherapy of Solid Tumors?

Abstract: Solid tumors are complex organ-like structures. The potential of normal neighboring cells to contribute to the initiation, progression and metastasis of epithelial-derived carcinomas has long been appreciated. However, the role of host cells has proven complex. Through multiple local and systemic mechanisms, nontransformed host cells can promote transition from a tumor-resistant to tumor-permissive environment, drive neoplastic transformation of epithelial cells, promote tumor growth, progression, and metastas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 136 publications
(137 reference statements)
2
79
0
Order By: Relevance
“…Another unique characteristic of PC is existence of high desmoplasia, which is suggested to promote lymphangiogenesis, metastasis and chemoresistance (22,24). It is also being explored as a factor that influences the balance between immune-dependent and immune-independent regulation of tumor growth (23). In our study, we observed an inhibitory effect of HNK on desmoplasia, as characterized by reduced secretion of extracellular matrix protein (collagen I) and diminished staining for myofibroblast marker (a-SMA).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Another unique characteristic of PC is existence of high desmoplasia, which is suggested to promote lymphangiogenesis, metastasis and chemoresistance (22,24). It is also being explored as a factor that influences the balance between immune-dependent and immune-independent regulation of tumor growth (23). In our study, we observed an inhibitory effect of HNK on desmoplasia, as characterized by reduced secretion of extracellular matrix protein (collagen I) and diminished staining for myofibroblast marker (a-SMA).…”
Section: Discussionmentioning
confidence: 60%
“…Extensive desmoplasia is a fundamental characteristic of pancreatic tumors, which has been suggested to be of significance from the pathobiological and clinical standpoints (22)(23)(24). Therefore, we next examined the effect of HNK on the desmoplastic reaction in orthotopic pancreatic tumors.…”
Section: Desmoplasia Is Decreased In Pancreatic Tumor Xenografts Of Hmentioning
confidence: 99%
“…Currently, several experimental therapies in the clinic aim to target the stroma. Indeed, most prominent are approaches with enzymes that aim to enhance the permeability of stroma (4,5,48). Our data show that these approaches can be very effective but can also have adverse effects that need to be considered before clinical development of new substances.…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, many more drugs are currently investigated in clinical trials, especially combination therapies aiming at the stromal compartment (4,5). These approaches act on the complex interactions in the tumor microenvironment, as we could show recently in macrophage-targeted immunotherapies (6).…”
Section: Introductionmentioning
confidence: 95%
“…However, in order to appropriately describe mechanisms of stromal immune regulation, it is also relevant to discuss the degree to which the "stromal compartment" actually represents a heterogeneous cellular population. Indeed, the work of Dr. Puré and colleagues reinforce the concept of stromal cell plasticity, suggesting stromal cells expressing fibroblast activation protein (FAP) represent a mesenchymal stem cell niche responsible for much of the local immunoregulatory signals compared to the terminally differentiated αSMA + myofibroblast (Lo, et al, 2015;Pure, et al, 2016). Multiple animal models have demonstrated enhanced antitumor immunity when FAP-expressing cells are conditionally depleted (Feig, et al, 2013) or therapeutically targeted (Lo, et al, 2015;L.…”
Section: Accepted Manuscriptmentioning
confidence: 99%